Evaluación de la calidad subjetiva de la carne cerdo, mediante técnicas de Qualitative Data Analysis (QDA), en el área metropolitana bonaerense /Evaluation of the subjective quality of pork, using Qualitative Data Analysis (QDA) techniques, in the metro - José María Aulicino; Andrea Beatriz Damico (Ciencia Veterinaria, 2018)
In Argentina, the consumption of pork meat is not proportional to international levels, nor does it express the productive potential of the country. Several factors intervene in this situation, myths and beliefs make up a status of lack of quality for consumption, thus it is not commonly consumed. Therefore, the objective of the present is to evaluate the perception of subjective quality  attributes of pork meat, using qualitative-quantitative techniques of discourse analysis of a group of consumers of the Buenos Aires suburbs. A focused discourse on the attributes was evidenced, in which ten qualities concepts emerged allowing a tight classification of the expressions, both positive and negative, from the inquired people. There was a difference in the perception of subjective quality between genders, age group and level of studies. In general, there is a positive assessment of men to the economic dimension, especially the youngest, but also the taste and low fat level, while women do it in the attributes of health dimension. Within the group of negative attributes the excess of fat arises, especially in consumers over 61 years old, the high price and bad taste in cases of 18 to 42 years old. Knowing the subjective perception about the quality of the food will allow to elaborate communication strategies on the benefits of the product and to minimize the impact of the beliefs on those negative attributes.